2015
DOI: 10.1186/s12889-015-1710-9
|View full text |Cite
|
Sign up to set email alerts
|

Linking social and built environmental factors to the health of public housing residents: a focus group study

Abstract: BackgroundPublic housing residents have a high risk of chronic disease, which may be related to neighborhood environmental factors. Our objective was to understand how public housing residents perceive that the social and built environments might influence their health and wellbeing.MethodsWe conducted focus groups of residents from a low-income public housing community in Baltimore, MD to assess their perceptions of health and neighborhood attributes, resources, and social structure. Focus groups were audio-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 25 publications
4
32
1
1
Order By: Relevance
“…Our project findings are similar to those of others, which point to a limited availability of social networks for women to draw on for social support (Hayward et al 2015). Lack of community cohesiveness specifically played an important role in the social supports available to women participating in the project.…”
Section: Discussionsupporting
confidence: 89%
“…Our project findings are similar to those of others, which point to a limited availability of social networks for women to draw on for social support (Hayward et al 2015). Lack of community cohesiveness specifically played an important role in the social supports available to women participating in the project.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, Hayward et al (2015) found that some residents experience a lack of trust with their neighbors in public housing communities which results in a lack of social support and connectedness. Perhaps the women did not have enough time to form trusting relationships with one another, but there is also the chance that they may not have the desire to build friendships with one another, given the transient nature of shelter living.…”
Section: Discussionmentioning
confidence: 99%
“…However, participants who resided in scattered public housing were more likely to state that their neighbors exercise more than the participants who resided in larger public housing developments (Pollack et al 2014;Hayward et al 2015).…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%
“…The HOPE VI grants directly influenced the lives of about 13,000 residents and their families; over 90% of these people were African Americans, about 80% were females, about half were ages 18 or below, and about 13% were ages 45 or older. (Curley 2010), little research discusses its potential impact on health behaviors (Pollack et al 2014;Hayward et al 2015), even though it is well documented that poor health is "an even bigger problem for HOPE VI families than lack of employment (Manjarrez et al 2007).…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation